Treatment of pemphigus vulgaris and foliaceus with efgartigimod, a neonatal Fc receptor inhibitor: a phase II multicentre, open-label feasibility trial - Goebeler, M.; Bata-Csörgő, Z.; De Simone, C.; Didona, B.; Remenyik, E.; Reznichenko, N. Yu.; Stoevesandt, J.; Ward, E. S.; Parys, W.; de Haard, H.; Dupuy, P.; Verheesen, P.; et al. (My University, 2022)
Background Pemphigus vulgaris and pemphigus foliaceus are potentially lifethreatening autoimmune disorders triggered by IgG autoantibodies against mucosal and epidermal desmogleins. There is an unmet need for fast-acting drugs that enable patients to achieve early sustained remission with reduced corticosteroid reliance. Objectives To investigate efgartigimod, an engineered Fc fragment that inhibits the activity of the neonatal Fc receptor, thereby reducing serum IgG levels, for treating pemphigus. Methods Thirty-four patients with mild-to-moderate pemphigus vulgaris or foliaceus were enrolled in an open-label phase II adaptive trial. In sequential cohorts, efgartigimod was dosed at 10 or 25 mg kg-1 intravenously with various dosing frequencies, as monotherapy or as add-on therapy to low-dose oral prednisone. Safety endpoints comprised the primary outcome. The study is registered at ClinicalTrials. gov (identifier NCT03334058). Results Adverse events were mostly mild and were reported by 16 of 19 (84%) patients receiving efgartigimod 10 mg kg 1 and 13 of 15 (87%) patients receiving 25 mg kg 1, with similar adverse event profiles between dose groups. A major decrease in serum total IgG and anti-desmoglein autoantibodies was observed and correlated with improved Pemphigus Disease Area Index scores. Efgartigimod, as monotherapy or combined with prednisone, demonstrated early disease control in 28 of 31 (90%) patients after a median of 17 days. Optimized, prolonged treatment with efgartigimod in combination with a median dose of prednisone 0 26 mg kg 1 per day (range 0.06–0.48) led to complete clinical remission in 14 of 22 (64%) patients within 2–41 weeks. Conclusions Efgartigimod was well tolerated and exhibited an early effect on disease activity and outcome parameters, providing support for further evaluation as a therapy for pemphigus.